2011
DOI: 10.1182/blood.v118.21.3358.3358
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Therapy in Non-Neoplastic Chronic Portal Venous Thrombosis in Cirrhosis: Recanalization and Liver Function Evaluation,

Abstract: 3358 INTRODUCTION: Non-neoplastic chronic portal vein thrombosis (PVT) is a frecuent diagnosis in the course of liver cirrhosis, with reported prevalences of 0.6% to 15,8%. PVT can motivate life-threatening complications due to worsening portal hypertension, so anticoagulation therapy is challenging in these patients. OBJECTIVE: To analyze the response to antithrombotic therapy and changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The sample size ranged from 16 to 182. Nineteen studies were published as full texts [ 14 , 20 37 ] and 14 as abstracts [ 38 51 ]. They were published between 2005 and 2019.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample size ranged from 16 to 182. Nineteen studies were published as full texts [ 14 , 20 37 ] and 14 as abstracts [ 38 51 ]. They were published between 2005 and 2019.…”
Section: Resultsmentioning
confidence: 99%
“…They were published between 2005 and 2019. Twenty of them were performed in Europe [ 21 25 , 30 , 32 36 , 38 40 , 42 , 44 , 46 , 47 , 49 , 50 ]. Fifteen studies were of prospective nature [ 22 25 , 28 , 30 , 31 , 36 , 38 , 39 , 41 , 44 , 45 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 studies were included in the final analysis [ 17 - 33 ]. Five studies reported on LMWH [ 17 , 22 , 23 , 25 , 32 ], 8 reported on VKA [ 19 - 21 , 24 , 26 , 27 , 29 , 33 ], and 3 reported on DOAC [ 26 , 29 , 31 ]. Two studies reported anticoagulation in general [ 18 , 30 ], and one study used danaparoid alone [ 28 ].…”
Section: Resultsmentioning
confidence: 99%